Counterion‐Induced Cationic Flexible Nanoparticle Catalytic of Piperidinolysis of Phenyl Salicylate. Issue 5 (31st May 2017) - Mohd Noh, Muhammad Azri; Khalid, Khalisanni; Ariffin, Azhar; Khan, M. Niyaz
Abstract: The removal of PSa − from bulk aqueous phase to the pseudo‐micellar phase by halobenzoate counterion X is responsible for the monotonic increase in kobs (pseudo first‐order rate constants) with the increase in the values of [MX] where MX = sodium salts of 2‐, and 4‐halobenzoic acids. The values of ion exchange constants, K X Br or R X Br for X = 2‐ and 4‐halobenzoate ions in the presence of tetradecyltrimethylammonium bromide (TTABr) were calculated from the apparent catalytic rate constants, X k cat which represent the catalytic effect of CFN. Larger values of K X Br or R X Br were observed for X = 4‐halobenzoate ions than that for X = 2‐halobenzoate ions due to isomeric factors. The values of K X Br or R X Br determined in the presence of TTABr were compared with previously determined K X Br or R X Br values in the presence of cetyltrimethylammonium bromide (CTABr). The values of K X Br or R X Br are nearly 8 ~ 9‐fold larger for 4‐IBz −, 4‐BrBz − and 4‐ClBz − compared to the respective values of X = 2‐IBz −, 2‐BrBz − and 2‐ClBz − . The values of K X Br or R X Br for X = 4‐FBz − is nearly 3‐fold larger than that for X = 2‐FBz − . The values of K X Br or R X Br for X = 2‐ and 4‐halobenzoates are significantly smaller in the presence of TTABr than these in the presence of CTABr nanoparticles.